Effect of the plasma excitation power on the properties of SiOxCyHz films deposited on AISI 304 steel - Santos, Nazir M. [UNESP] (2017)
Films were produced on stainless-steel substrates by radiofrequency Plasma Enhanced Chemical Vapor Deposition (RF-PECVD) of mixtures containing 70% hexamethyldisiloxane, 20% oxygen and 10% argon. While the plasma excitation power was varied from 15 to 75 W, the deposition time and total gas pressure were kept constant at 1800 s and 8.0 Pa, respectively. The influences of the plasma power on the plasma kinetics and the ion bombardment of the growing film are discussed. Film composition and chemical structure were determined using X-ray photoelectron- and infrared reflectance-absorbance spectroscopy, respectively. Profilometry was used to measure the thicknesses of the resulting layers. The root mean square roughness was evaluated from surface topographic profiles acquired by atomic force microscopy. Scanning electron microscopy and energy dispersive spectroscopy were employed to evaluate the morphology and elemental composition of the coatings. Electrochemical impedance spectroscopy and potentiodynamic polarization tests were used to derive the corrosion resistance of the samples to a saline solution. Substantial changes in the material structure and progressive increases in film thickness were observed with increasing applied power. The resulting material was an organosilicon layer composed of Si[sbnd]O backbones surrounded by methyl groups, very similar to conventional polydimethylsiloxane. Increases in the proportions of Si[sbnd]O and methylsilyl groups in the structure were observed at greater plasma excitation powers, indicating densification of the structure owing to greater ion bombardment. The surface morphology and roughness were also dependent on the treatment power. Independently of the deposition conditions, application of the film increased the corrosion resistance of the stainless steel. A 10,000-fold elevation in the total system resistance under electrochemical testing was achieved for the film prepared with the greatest ion bombardment intensity. Film thickness was observed to be a key parameter but the coating structure had a major effect on this result.